(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study examines the asymmetric effect of changes in credit portfolio quality on the adequacy of loan loss provisions in Syrian conventional banks during 2011–2024. It adopts an analytical auditing perspective that links credit default indicators with the reasonableness of accounting estimates. The study uses balanced annual panel data for 11 banks listed on the Damascus Securities Exchange and applies the PMG-NARDL model to decompose positive and negative shocks in the ratio of non-performing loans to total loans. The loans-to-assets ratio and the market-to-book ratio are included as control variables. The empirical tests show cross-sectional dependence, a suitable integration structure, slope homogeneity, and cointegration supported by the Westerlund test. The Dumitrescu-Hurlin causality test indicates one-way causality from non-performing loans to provision adequacy. The results confirm significant long-run asymmetric effects, while short-run effects remain insignificant due to the cumulative nature of provisioning and possible timing mismatch in accounting measurement. Robustness checks using an alternative provision adequacy measure support the main findings.